2017
DOI: 10.17268/sci.agropecu.2017.04.06
|View full text |Cite
|
Sign up to set email alerts
|

YY super males have better spermatic quality than XY males in red tilapia Oreochromis niloticus

Abstract: The influence of sex-related chromosomal arrangement in an YY and XY population of Oreochromis niloticus males was investigated in this study. A better spermatic mobility, motility, viability, confluence and less abnormality were found in double Y-chromosome males (YY-males), compared to XY-males; however, this better spermatic quality did not correlate with the body weight of individuals which was significantly better in XY-males. This study establishes the influence of YY-related sequences over spermatic qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
4
7
0
Order By: Relevance
“…), but for the progeny of sex‐reversed fish no such reduction has been identified (e.g., Salirrosas et al. ). Currently, the physiological performance of stocked M YY Brook Trout relative to wild males (as determined by sperm quality) is uncertain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…), but for the progeny of sex‐reversed fish no such reduction has been identified (e.g., Salirrosas et al. ). Currently, the physiological performance of stocked M YY Brook Trout relative to wild males (as determined by sperm quality) is uncertain.…”
mentioning
confidence: 99%
“…In addition, the success of an M YY stocking program requires that the M YY fish mature at a high rate and spawn at a similar time as wild fish, and that the testes and milt of M YY fish perform similarly to those of their wild counterparts. Existing research suggests that sex-reversed fish have reduced reproductive abilities relative to wild males (e.g., Senior et al 2014), but for the progeny of sex-reversed fish no such reduction has been identified (e.g., Salirrosas et al 2017). Currently, the physiological performance of stocked M YY Brook Trout relative to wild males (as determined by sperm quality) is uncertain.…”
mentioning
confidence: 99%
“…It is difficult to predict the impact of hormone use on the environment and human health. GMT is an ideal substitute for hormonal treatment and has been investigated extensively (J. Chen, Fan, Tan, Jiang, & Wang, 2018Gennotte et al, 2015;Mair et al, 1995;Salirrosas et al, 2017;Sultana et al, 2020;Sun et al, 2014). Sex-specific or sex-linked markers accelerated the development of this technology in multiple strains of Nile tilapia.…”
Section: Discussionmentioning
confidence: 99%
“…Because Marker-5 is located on the same Fosmid clone as amhy, separated by a small physical distance, it is considered as a sex-specific marker in Nile tilapia. Marker-5 and derived or similar markers have been used to test the sex genotype of laboratory strains, cultured strains, as well as wild populations (Salirrosas et al, 2017;Sissao et al, 2019;Sultana, Khan, Hossain, & Alam, 2020;Zhao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of initial reproduction potential, gonads of sex‐reversed fish can function well. For example, M YY fish had better spermatic quality than normal XY males in Nile Tilapia Oreochromis niloticus (Salirrosas et al 2017), and F YY fish had slightly higher fecundities than standard XX females in a YY male Brook Trout broodstock (Schill et al 2016). We further assumed that both stocked and wild carp randomly selected mates in proportion to their relative abundance (Gutierrez and Teem 2006; Teem and Gutierrez 2010).…”
Section: Discussionmentioning
confidence: 99%